2015
DOI: 10.3390/toxins7062051
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential of Venom from Nasonia vitripennis as Therapeutic Agent with High-Throughput Screening Tools

Abstract: The venom from the ectoparasitoid wasp Nasonia vitripennis (Hymenoptera: Pteromalidae) contains at least 80 different proteins and possibly even more peptides or other small chemical compounds, demonstrating its appealing therapeutic application. To better understand the dynamics of the venom in mammalian cells, two high-throughput screening tools were performed. The venom induced pathways related to an early stress response and activated reporters that suggest the involvement of steroids. Whether these steroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Recent examples of the use of high-throughput assay screening on venoms include the analysis of the venom from the wasp Nasonia vitripennis , which has indicated that it might have therapeutic potential. The use of reporter arrays showed the venom altered the expression of nuclear factor κβ (NF-κB) signalling pathway genes that have a role in inflammatory diseases and cancer [ 69 ]. Furthermore, a combined cytotoxicity screening and venom profiling approach on snake venom revealed the presence of activity against a human lung carcinoma cell line, and identification of a range of proteins including phospholipases and serine proteases [ 70 ].…”
Section: Venomicsmentioning
confidence: 99%
“…Recent examples of the use of high-throughput assay screening on venoms include the analysis of the venom from the wasp Nasonia vitripennis , which has indicated that it might have therapeutic potential. The use of reporter arrays showed the venom altered the expression of nuclear factor κβ (NF-κB) signalling pathway genes that have a role in inflammatory diseases and cancer [ 69 ]. Furthermore, a combined cytotoxicity screening and venom profiling approach on snake venom revealed the presence of activity against a human lung carcinoma cell line, and identification of a range of proteins including phospholipases and serine proteases [ 70 ].…”
Section: Venomicsmentioning
confidence: 99%
“…In this study, we examined the diversity of P. vindemmiae venom compositions based on both transcriptome-sequencing and proteome analysis, and compared it to venoms of three parasitoid families. Given the amazing toolkit available in its host drosophilids, we propose that future studies combining the power of Drosophila as a model system with its ectoparasitoid P. vindemmiae have great potentials for advancing our understanding of the functions and evolution of venom proteins, and assessing their pharmacological possibilities (Danneels et al, 2010(Danneels et al, , 2015Moreau and Asgari, 2015;Huerta-Rey et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Parasitoid wasps are the largest group of venomous animals, with somewhere between 100 000 and 500 000 species, but have been relatively understudied in venom research (Godfray, ; Quicke, ). These venoms are potentially a treasure trove of resources and potential targets for drug therapy for different diseases (Piek, ; Danneels et al ., ; Mrinalini and Werren ); however, a first step of this process is to understand the evolution and function of these venoms in their natural systems.…”
Section: Resultsmentioning
confidence: 99%
“…More recent studies using genome‐wide approaches have also found that envenomated fly hosts remain alive and transcriptionally active for over 5 days, and exhibit transcriptional changes that correspond to metabolic, immune response and developmental phenotypes (Danneels et al ., ; Martinson et al ., ; Siebert et al ., ). Yet most of the previous work has focused on whole venom effects in N. vitripennis , whereas relatively few studies have focused on specific venom proteins (However see Danneels et al ., ; Siebert et al ., ; Martinson et al ., ).…”
Section: Introductionmentioning
confidence: 99%